PEGylated Molybdenum-Iodine Nanocluster as a Promising Radiodynamic Agent against Prostatic Adenocarcinoma - Přibyl, Tomáš; Rumlová, Michaela; Mikyšková, Romana; Reiniš, Milan; Kaňa, Antonín; Škoch, Karel; Zelenka, Jaroslav; Kirakci, Kaplan; Ruml, Tomáš; Lang, Kamil (Inorganic chemistry, 2024)
The combination of photodynamic therapy and radiotherapy has given rise to a modality called radiodynamic therapy (RDT), based on reactive oxygen species-producing radiosensitizers. The production of singlet oxygen, O2(1Δg), by octahedral molybdenum (Mo6) clusters upon X-ray irradiation allows for simplification of the architecture of radiosensitizing systems. In this context, we prepared a radiosensitizing system using copper-free click chemistry between a Mo6 cluster bearing azido ligands and the homo-bifunctional linker bis-dPEG11-DBCO. The resulting compound formed nanoparticles, which featured production of O2(1Δg) and efficient cellular uptake, leading to remarkable photo- and radiotoxic effects against the prostatic adenocarcinoma TRAMP-C2 cell line. Spheroids of TRAMP-C2 cells were also used for evaluation of toxicity and phototoxicity. In vivo experiments on a mouse model demonstrated that subcutaneous injection of the nanoparticles is a safe administration mode at a dose of up to 0.08 g kg-1. The reported results confirm the relevancy of Mo6-based radiosensitizing nanosystems for RDT.
Keywords: myši; Iodine; jod; adenokarcinom; fotochemoterapie; zvířata; Mice; Molybdenum; Polyethylene Glycols; molybden; Photochemotherapy; Adenocarcinoma; polyethylenglykoly; Animals